Exploring the embodied subtleties of collaborative creativity: What organisations can learn from dance - Satama Suvi; Blomberg Annika; Warren Samantha (Sage, 2022)
This study illustrates the value of embodied subtleties in the process of collaborative creativity. Drawing on a sensory ethnography of two dance productions, we illustrate the fine-grained ways in which professional dancers negotiate creative processes behind the scenes. We identify three aspects through which collaborative creativity emerges from bodily subtleties: (1) moving beyond individual bodies towards collective ambitions, (2) relating to colleagues’ micro-gestures and bodily nuances, and (3) the role of ‘serious play’ between bodies in setting the scene for the first two aspects to occur. The findings will contribute to our understanding of the practice of collaborative creativity, which we treat as not only a mental but also a highly intimate bodily practice. We conclude that appreciating sensory micro-dynamics between oneself and one’s colleagues is crucial for creative collaboration, which is increasingly necessary for management learning in contemporary organisations.